Perancangan Sistem Informasi Pengolahan Data Kematian Berbasis Web Guna Menunjang Efektivitas Pelaporan Mortalitas - Ramadhan, Fadhlurrahman Dwi; Abdussalaam, Falaah; Sari, Irda (Program Studi Teknik Informatika Universitas Pamulang, 2024)
The advancement of information technology is growing rapidly. One of the benefits that can be felt is the increasing development of medical records in hospital. With the existence of electronic medical records, the quality of service in hospitals can be better, effective and efficient. As in XYZ Hospital, the medical records used in general are electronic-based, but there are still several reports that are still done ineffectively because they still use google spreadsheets and have to move data one by one, one of which is Patient Death Reporting. This makes the process of preparing death reports take quite a long time. To fix this problem, it is necessary to design a patient death reporting information system to facilitate and speed up the preparation of death reports. The design method that will be made uses waterfall and web-based. With this information system created, it will make it easier for officers to make death reports and the time used can be more effective.